The Bubble-Wrap Peritonsillar Abscess Model - Nur-Ain Nadir; Clint B LeClair; Matthew Fischer; Michael Craddick (eScholarship Publishing, University of California, 2017)
Audience: The Bubble-Wrap Peritonsillar Abscess Model is designed to instruct PGY 1-4 Emergency Medicine residents as well as Emergency Medicine-bound students. Introduction: Peritonsillar Abscesses (PTA) are frequently encountered in clinical practice. Emergent ENT consultation may not be possible. Emergency physicians must be able to perform needle aspiration of PTA. This procedure is fraught with risk due to the natural proximity of the internal jugular vein and carotid artery to the pharyngeal tonsils. Deliberate practice of clinical procedures can drastically reduce associated complications (Okuda et al., 2009); however, no simulators are available for this particular purpose. Here we describe a PTA model that can be used to practice PTA drainage by novice learners. Objectives: The basic purpose of the bubble-wrap PTA model is to teach learners competency in the needle aspiration of peritonsillar abscesses. Method: This model uses bubble wrap, zip ties, chicken broth and liquid latex to simulate a peritonsillar abscess. Learners are then able to perform a needle aspiration of the simulated abscess from start to the end with no risk to a live patient.